Advances in the diagnosis of Ascaris suum infections in pigs and their possible applications in humans. Issue 14 (24th April 2014) - VLAMINCK, JOHNNY; LEVECKE, BRUNO; VERCRUYSSE, JOZEF; GELDHOF, PETER
SUMMARY: Ascariasis is one of the most common parasitic diseases in both humans and pigs. It has been shown to cause growth deficits in both species and to impair cognitive development in children. Notwithstanding its substantial impact on pig economy and public health, diagnosis of ascariasis has mostly relied on the detection of eggs in stool and further development of novel, more sensitive methods has been limited or non-existent. Here, we discuss the currently available techniques for the diagnosis of ascariasis in pigs, their caveats, and the implications of a new serological detection technique for the evaluation of both pig and human ascariasis.